Effect of Oil Type in Soap Production with Its Implication on Quality and Cost of Production - Bashirat Abdulsalam,; Dauda Hassan Lamuntani,; Mohammed Momodu Lawal, (International Journal of Scientific Research in Science and Technology, 2024)
The study examined the effect of oil - type in soap production. An attempt was made to identify the oil-type that is suitable and applicable in quality soap production. Three types of oil were used for soap production, namely, palm kernel oil, coconut oil and groundnut oil. The soap produced with each oil was subjected to test for lather formation, pH and texture test to determine their quality. Palm kernel oil and coconut oil soaps exhibit pH value of 9 each and groundnut oil soap exhibits pH value of 10. Palm kernel oil soap forms lather readily followed by coconut oil and lastly ground groundnut oil. Palm kernel oil produced the hardest soap followed by coconut oil and the least is groundnut oil. This shows that palm kernel and coconut oils produced a better quality soap in terms of lather formation. Their pH Value also show that their soap is less caustic and safe to use on both fabric and skin and their texture show that they last long for laundry which indicates their economic value.
Keywords: Palm Kernel Oil; Coconut Oil; Groundnut Oil